Analisis Komunikasi Internal Karyawan di HW Hotel Padang - Fitri, Hikmah; Kasmita, Kasmita; Afni, Fauza (Departemen Pariwisata Universitas Negeri Padang, 2024)
This research was motivated by the lack of internal employee communication, resulting in decreased employee performance. This study aims to determine internal communication at HW Hotel Padang. This type of research is descriptive research with quantitative data with survey methods. The population in this study was all employees of HW Hotel Padang, totaling 45 people with a sampling technique using total sampling. The data in this study used primary data and secondary data. The data collection technique used is a questionnaire that is arranged before. Instrument trials use validity tests and reality tests. The data was analyzed using SPSS program version 25.00. The results of this study are the results of respondents' achievements in the downward communication dimension (74%) categorized as good, which concluded that leaders almost all the time give orders to employees to do every task but the attitude of superiors when providing information is not right. The results of respondents' achievements in the upward communication dimension (63.85%) are categorized as sufficient, where employees almost routinely submit reports after doing work, it's just that employees have little difficulty conveying aspirations about work-related matters. The results of respondents' achievements on the diagonal communication dimension (79.95%) are categorized as good, where employees as a whole are responsible for the work given, it's just that sometimes employees find it difficult to understand the message given.